Straw economics and communication: a new distribution of the value of information in the era of creativity - Zaganelli, Bárbara Martins; Gantos, Marcelo Carlos (Organicom, 2015)
In view of the crisis of traditional forms of communication and the boom of social networking and alternative media basedon digital convergence, one discusses the process of (re)arrangement of the scenario of communication and the currentchallenges of the media, thinking about a new way for distribution of the information under the straw economics bias, i.e.,by the economics of culture and creativity. One expects to contribute to an analysis of the impact of straw economics on thecommunications scenario, the progresses and the impasses.